Grade-Three Students’ Use of Print and Electronic Resources - Nesset, Valerie (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
As part of a larger study into the information behaviour of grade-three students the use of books and the Internet as information sources was investigated. During class time books and other printed sources were used more often than the Internet. This paper looks at possible reasons why. Faisant partie d’une vaste étude du comportement informationnel des enfants de troisième année, l’utilisation des livres et d’Internet comme sources d’information a été explorée. Les livres de classe et d’autres sources imprimées sont utilisés plus fréquemment qu’Internet. Cette communication présente les raisons possibles expliquant ce résultat.